(untitled) (Environmental Smoke, 2025)
The demand for better veterinary care is growing as the number of animals reaching greater longevity increases. Many programs to raise awareness about better veterinary care are being carried out around the world, which is fueling demand and is no different in Brazil. Such initiatives create awareness between pet owners and veterinary care, which should boost the market. Marketing applied to the veterinary market uses a variety of strategic initiatives to achieve its growth targets and expand its market share. Major companies are launching new products, forming partnerships and collaborations, expanding their local and regional presences and pursuing mergers and acquisitions. Thus, it is hoped that marketing, as addressed in this article, will boost professionals in the field in their diverse realities.